Raising Your Kids Right : Children's Literature and American Political Conservatism. - Abate, Michelle Ann, 1975- (Rutgers series in childhood studies., 2010)
Highlighting the works of William Bennett, Lynne Cheney, Bill O'Reilly, and others on the American political right, Michelle Ann Abate brings together such diverse fields as cultural studies, literary criticism, political science, childhood studies, brand marketing, and the cult of celebrity. Raising Your Kids Right dispels lingering societal attitudes that narratives for young readers are unworthy of serious political study by examining a variety of texts that offer information, ideology, and even instructions on how to raise kids right, not just figuratively but politically.